Rhabdomyosarcoma of The Uterine Cervix: Case Report and Literature Review - Tatit Nurseta; Ayu Rizky Widowati (Asian Journal of Health Research, 2023)
Introduction: Embryonal rhabdomyosarcoma (RMS) of the uterine cervix is aÂ  rare mesenchymal tumor that occurs in less than 1% of all cervical cancers. These malignant tumors occur in adolescents and young adults. It starts from embryonic muscle tissue or pluripotent mesenchymal cells. This case reports an unusual case of embryonal rhabdomyosarcoma in a 33-year-old woman. Case Presentation: A 33-year-old woman came to the Obstetrics and Gynecology Department. She complained with exophytic cervical masses and vaginal bleeding. There were no remarkable findings about medical, family, and social history Histopathology confirms embryonal rhabdomyosarcoma (sarcoma botryoides) of the uterine cervix. A combination of radical hysterectomy and adjuvant chemotherapy was chosen as the therapeutic option in this case. Conclusion: Although the prevalence of cervical rhabdomyosarcoma in adults is very low, a multimodality approach is necessary for favorable prognostic.